PERTANGGUNGJAWABAN PIDANA KORPORASI SEBAGAI PENYELENGGARA SISTEM ELEKTRONIK DALAM TERJADINYA KEBOCORAN DATA PENGGUNA SISTEM ELEKTRONIK - Rony Mart Panjaitan (Fakultas Hukum Universitas Tarumanagara, 2021)
Based on reliable sources, it is to be found that Indonesia has experienced an increase in the number of active internet users between the time period of 2020 to 2021 with an estimate of 27 million users. Not forgetting the dangers of personal data leakage also goes hand in hand. One of the main factors that can pose a danger of personal data leakage is the lack of digital security in Indonesia, creating loop holes for telematics crimes. However, this does not rule out the possibility that the leakage of public personal data is carried out or caused by the corporation operating the internet system. This study examines the form of corporate criminal liability for electronic system operators in relation to the leakage of user data. The type of research used is prescriptive normative which is generally used to identify the law in accordance with legal principles in Indonesia. The research approach used is a conceptual approach, which refers to legal principles based on legal doctrine. Reinforced by sources, this research also uses primary, secondary and non-legal materials. Through this research we get to generate the idea of investigating data leakage occurrence through forensic examination, which may help us in identifying whether corporation managing the system is responsible of the criminal act or not. In this case, the corporation can be sentenced based on Article 52 of the Electronic Information and Transaction Law, if the corporation is found guilty, then the corporation must carry out administrative sanctions in accordance with the Electronic Information and Transaction Law and Government Regulations 71 of 2019. However, there are a few obligations in proving the same such as difficulty in proving the element of offense violated by the corporation and the fact that Indonesia highly upholds the principle of legality, which is one of the challenges in dealing with computer crime